Differential Effects of Natural Grazing and Feedlot Feeding on Yak Fecal Microbiota - Shah, Tariq; Ding, Luming; Ud Din, Ahmad; Hassan, Faiz-ul; Ahmad, Anum Ali; Wei, Haiyan; Wang, Xianju; Yan, Qi; Ishaq, Muhammad; Ali, Niyaz; Fang, Yougui (Frontiers in Veterinary Science, 2022)
Variation in food and diet shapes the diversity of the gut microbiota of ruminants. The present study investigated the microbial diversity in the fecal microbiota of Yaks reared under natural grazing and feedlot system. A total of forty-eight domestic yaks having an average age of 7.5 years were selected from two different grazing habitats: one grazed natural pasture (grazing yaks - GY) and one group were fed fodder and concentrate (feedlot yaks - FY). Crude protein, non-fiber carbohydrate, hemicelluloses and digestible dry matter contents of natural pastures were higher than those in the feedlot. The lower insoluble fiber contents were found in grazing land. The 16S rRNA gene sequencing revealed 675 and 348 unique Operational taxonomic units (OTUs) in the GY and FY, respectively in addition to 1778 common OTUs. Overall, a total of 9891 OTUs were identified as a whole, of which 6160 OTUs were from GY and 3731 from FY. Shannon index analysis revealed a higher bacterial diversity in GY than FY. At the phylum level, Firmicutes were dominant bacterial taxa in both groups. The Firmicutes in GY (56% ± 0.05) were higher than in FY (41% ± 0.08). At the family level, GY had a significantly higher abundance of Ruminococcaceae, (p < 0.001) and Rikenellaceae (p < 0.001) than FY but FY had a significantly higher abundance of Prevotellaceae than GY (p < 0.001). At the genus level, abundances of Faecalibacterium, Alloprevotella and Succinivibrio were higher in FY than in GY. This study presents novel information on faecal bacterial composition and diversity in yaks reared under two different production systems.